Increase in circulating GLP-1 following low FODMAP diet in irritable bowel syndrome patients - Khan, Umael; Brønstad, Ingeborg; Hillestad, Eline Margrete Randulff; Steinsvik, Elisabeth K.; Hausken, Trygve; Berentsen, Birgitte; Lied, Gülen Arslan (Frontiers in Nutrition, 2025)
BackgroundFermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) as well as glucagon-like peptide-1 (GLP-1) have independently been implicated in irritable bowel syndrome (IBS) pathophysiology. However, there is a lack of studies that assess how low FODMAP diet affects circulating GLP-1 levels in IBS patients.MethodsThirty patients with either diarrhea or mixed type IBS were recruited and undertook low FODMAP diet for 12 weeks. Plasma GLP-1 levels, IBS Severity Scoring System (IBS-SSS), body weight and FODMAP intake were assessed before and after the 12-week dietary intervention.Key resultsFollowing a low FODMAP diet, average IBS-SSS and body weight were reduced (p < 0.01) and plasma GLP-1 level was increased (p = 0.027).ConclusionOur study indicates that a 12-week low FODMAP diet may increase plasma glucagon-like peptide-1 levels in IBS patients. The underlying mechanism for this increase remains to be understood.